Fabrication of anti-dripping and flame-retardant polylactide modified with chitosan derivative/aluminum hypophosphite. (15th December 2022) - Wang, Yadong; Yuan, Jun; Ma, Li; Yin, Xianze; Zhu, Zongmin; Song, Pingan
Abstract: As a very promising biodegradable polymer, polylactic acid (PLA) has been applied in various fields. Unfortunately, the disadvantages of flammability and large amounts of molten droplets limit its application. In this work, we constructed a novel flame-retardant system by combining the as-prepared bio-based chitosan derivative (CS-TE) and aluminum hypophosphite (AP), and used it to improve the flame retardancy and anti-dripping property. When 3.75 wt% CS-TE and 11.25 wt% AP were incorporated into PLA, the PLA composite had a limiting oxygen index of 28.5 % and achieved a UL-94 V-0 rating as well as showed excellent anti-dripping behavior. Meanwhile, the peak heat release rate and total smoke production decreased by 52.3 % and 73.4 % respectively. Graphical abstract: Unlabelled Image